Respostas
respondido por:
0
6x² + 43x - 40 = 0
Δ = b² - 4ac
Δ = 43² - 4 . 6 . (-40)
Δ = 1849 + 960
Δ = 2809
x1 = -b + √Δ / 2a
x1 = -43 + √2809 / 2 . 1
x1 = -43 + 53 / 2 = 10/2 = 5
x2 = -b - √Δ / 2a
x2 = -43 - √2809 / 2 . 1
x2 = -43 - 53 / 2 = -96/2 = -48
Δ = b² - 4ac
Δ = 43² - 4 . 6 . (-40)
Δ = 1849 + 960
Δ = 2809
x1 = -b + √Δ / 2a
x1 = -43 + √2809 / 2 . 1
x1 = -43 + 53 / 2 = 10/2 = 5
x2 = -b - √Δ / 2a
x2 = -43 - √2809 / 2 . 1
x2 = -43 - 53 / 2 = -96/2 = -48
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás